ChemInform Abstract: Baeyer—Villiger Rearrangement of a Substituted Pyrrole by Oxone. Issue 46 (18th November 2014) - Kao, Joseph P. Y.; Muralidharan, Sukumaran; Zavalij, Peter Y.; Fletcher, Steven; Xue, Fengtian; Rosen, Gerald M.
Abstract Treatment of the highly substituted pyrrole (I) with Oxone in ethanol results in the formation of unexpected dearomatized product (III) via Baeyer—Villiger‐type oxidation and subsequent rearrangement.